Mexican American Adolescents’ Cultural Orientation, Externalizing Behavior and Academic Engagement: The Role of Traditional Cultural Values - Gonzales, Nancy A. (2008)
This study of 598 7(th) grade students of Mexican origin examined the role of traditional cultural values as a mediator of the effects of immigrant status, Mexican cultural orientation and Anglo cultural orientation on adolescent externalizing behavior and academic engagement. Immigrant status of adolescents and their maternal caregivers uniquely predicted increased Mexican cultural orientation and decreased Anglo cultural orientation, and both Mexican and Anglo cultural orientation related positively to adolescents” endorsement of traditional cultural values. Endorsement of traditional cultural values related, in turn, to decreased externalizing behaviors and increased academic engagement and these findings were replicated across adolescent and teacher report of these two outcomes. Tests of mediation provided further evidence to support these pathways. Findings support the central importance of traditional cultural values as a protective resource that explains why immigrant youth exhibit fewer externalizing problems and increased academic engagement when compared to their second and third generation peers.